Contemporary Islamic of Radical Movement (ISIS and Its Impact on Indonesia) - Musadad, Ahmad; Zahro, Umi Indasyah; Syamsi, Ahmad Badarus; Pujiati, Tri; Syaifudin, Mochamad (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This research was conducted to provide an overview of the radical Islamic movement that followed the WTC tragedy. This movement had a tremendous impact on Indonesia as a country with a majority Muslim population. The impact of this radical movement has made Islam's image less good in the eyes of the world and it is considered a terrorist who preaches violence. It is hoped that this research will be able to provide an overview of the radical movement carried out by ISIS which has had an impact on the worldview of Muslims in Indonesia. This research with a qualitative descriptive design uses library research by looking for references from books and journals that are relevant to contemporary Islamic radical movements. The results of this research show that ISIS is part of the dark history of Islam which grew and grew out of political-based radicalism as a continuation of the violent and intolerant ideology of neo-khawarijism. Therefore, it is necessary to have a genuine understanding of Islam so that radical movements that are detrimental to Islam will no longer emerge in Indonesia or in the world.